Shaykh Ibrāhīm Inyās: The Influence of His Mystical Sojourn In Nigeria - Adenigba, Sikiru (Al-Basirah Journal, 2023)
The contributions of Shaykh Ibrahim Inyas in mystism and Islam can not be over emphasized. Shaykh Ibrahim Inyas, a Sufi of twenthieth centuary and a leader of Tijaniyyah who engaged in the field of propagation of Islam and Sufism in West Africa including Nigeria. Shaykh Ibrahim had contact with north and south west Nigeria in 1937 and 1951 respectively. The objective of this paper therefore, is to examine his propagation of Sufism and Islam with his scholarly works in different fields of learning. The paper also discusses the influence of his mystical sojourn on Nigerian Muslims. The paper adopts historical and analytical methods. The paper revealed that shaykh Ibrahim Inyas is a real propagator of Islam and Sufism who influenced many Nigerian Muslims spiritually educationally. The paper concludes that Shaykh Ibrahim Inyas has contributed to the development of Muslim Spirituality in Nigeria. The paper recommendes that the Sufis of nowadays should emulate Ibrahim Inyas’s method of propagation of Islam and not deviate from the original path laaid down by the Shaykh and his predecessors.